1987
DOI: 10.1254/jjp.43.143
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic denervation supersensitivity in the rat iris sphincter muscle : An in vitro study.

Abstract: Abstract-Supersensitivity in chronically sympathectomized smooth muscle has long been studied, but little is known about chronically parasympathectomized smooth muscles.Iris is one of the few smooth muscle organs which can be para sympathetically denervated. We used rats because the denervation supersensi tivity in the vas deferens has extensively been studied in this species.The rat was unilaterally ciliary-ganglionectomized.After 1-13 days, strips of the iris sphincter muscle obtained from denervated eye wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It is notable that not only the maximum response to high K+ but also the sensitivity to extracellular Ca2+ was markedly increased. These are exactly the same as the results obtained by parasympathetic denervation by ciliary ganglionectomy (Hasegawa et al ., 1987). The mechanisms, however, underlying the nonspecific supersensitivity by the AF64A injection were not further examined in the present study .…”
Section: ) Effects Of Af64a Added In Vitro On Contractile Responses supporting
confidence: 91%
See 2 more Smart Citations
“…It is notable that not only the maximum response to high K+ but also the sensitivity to extracellular Ca2+ was markedly increased. These are exactly the same as the results obtained by parasympathetic denervation by ciliary ganglionectomy (Hasegawa et al ., 1987). The mechanisms, however, underlying the nonspecific supersensitivity by the AF64A injection were not further examined in the present study .…”
Section: ) Effects Of Af64a Added In Vitro On Contractile Responses supporting
confidence: 91%
“…An increase in the sensitivity of the contractile proteins by a change in the activity or amount of calmodulin has been proposed to explain the supersensitivity induced by the sympathetic denervation (Ramos et al, 1986). Similar possibility has been suggested in parasympathectomized iris sphincter or dilator (Hasegawa et al, 1987Banno et al, 1987Hashimoto et al, 1993. Further experiments are required , especially using skinning tech niques, to elucidate the mechanisms for AF64A-induced nonspecific supersensitivity.…”
Section: ) Effects Of Af64a Added In Vitro On Contractile Responses mentioning
confidence: 58%
See 1 more Smart Citation
“…At the start of the experiment, resting tone was adjusted to 10 mg and 50 mg in the dilator and sphincter muscles, respectively. Marmfors & Nilsson (1964) as modified by Hasegawa et al (1987) and Hashimoto et al (1993). Since the changes in drug-sensitivity reached steady levels about 2 to 3 days after ciliary ganglionectomy, the denervated dilator muscles were used in experiments 1 week after the operation (Hasegawa et al, 1988).…”
Section: Preparationmentioning
confidence: 99%
“…In the present study, we investigated the mechanism of action of nicotine in an isolated iris sphincter preparation of rabbit, which, exceptionally, is densely innervated by parasympathetic neurones and free of ganglia (Schaeppi, 1966;Hasegawa et al, 1987). Since it has recently been reported that there are capsaicin-sensitive primary sensory neurones in isolated preparations (Ueda et al, 1981;, the effect of nicotine on the sensory nerve terminals was also studied.…”
Section: Introductionmentioning
confidence: 99%